The Communication Strategy of Government in Bulu Cina Village towards Prosperous Village - Cut Alma Nuraflah (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Not only the city government, the village government is currently required to be independent and carry out all the functions of its own government including in determining various policies strategies, and in this case is the communication strategy. A good and effective communication strategy implemented by the village government aims to bring the village towards a prosperous village. This research looks at how the strategy carried out by Bulu China village government in realizing a prosperous village. Using a qualitative approach, this research was conducted in Bulu Cina Village, Hamparan Subdistrict, North Sumatra. Data collection techniques with interview methods on 3 State apparatus, observation and study documentation. Data were then analyzed using Miles Huberman analysis. The results obtained from this study indicate that Bulu Cina Village Government in realizing prosperous village has not conducted a good communication strategy to create prosperous village so that the obstacles in implementing the program plan are still encountered by Bulu Cina village government.